The Challenges of Forming A Culture of Change in Iraq (Self-Obstacles to the Media Role) - Wadi Hamood, Jaleel (ALBAHITH ALALAMI, 2014)
The Iraqi culture faced a set of challenges that can be diagnosed with the most prominent features as follows: • The dominance of authoritarian political systems which entails authoritarian regimes with the absence of contemporary political concepts of human rights. • The prevalence of non- informed cultural systems which have the shortage of capabilities that enable them to activate cultural elements in positive references, historical, or seclusion on itself and not be able to interact with the current active cultures. • Stagnant economic conditions have not had a decent life for individuals, or a certain level of well-being, as well as poor services and others. • Social life controlled by the prevailing culture, limiting the capacity of human creativity, and deprive him of his freedom to enjoy, imposing different types of wills that are composed as a religious or political form. Although the Iraqi area creates an interactive media long time ago, since the sixties of the nineteenth century, however, these events have not been able to perform roles that are supposed to do, namely the development of a culture of change, and in this aspect is the research problem, which seeks in its main target to detect obstacles that have limited the role of the media in shaping the culture of change and the development of awareness of the change